2010
DOI: 10.1560/ijee.56.3-4.251
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Ecology Framework for Understanding Vector and Vector-Borne Disease Dynamics

Abstract: The integration of community ecology into the understanding and management of vectors and vector-borne diseases has largely occurred only recently. This compendium examines a variety of community interactions that can affect vector or vector-borne disease dynamics. They include: the importance of risk of predation, risk of ectoparasatism, competition, interactions of competition with transgenic control, apparent competition mediated through vectors, indirect effects of pesticides, vector diversity, and parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Like many parasites, this archetypal case study for host diversity generating a dilution effect (Lyme disease) has multiple vector species, yet the influence of vector diversity on disease risk is underappreciated (Blaustein et al 2010;Godfray 2013). Variation in the distribution, life history, and behavior of vectors will influence each species' capacity to transmit disease (i.e., vector competence; table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Like many parasites, this archetypal case study for host diversity generating a dilution effect (Lyme disease) has multiple vector species, yet the influence of vector diversity on disease risk is underappreciated (Blaustein et al 2010;Godfray 2013). Variation in the distribution, life history, and behavior of vectors will influence each species' capacity to transmit disease (i.e., vector competence; table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Although such interactions occur for vectors of animal and plant pathogens (Blaustein et al. , Johnson et al. ), we focused on plants, given the substantial empirical data assessing effects of species interactions on movement and vital rates of plant‐pathogen vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have in turn assessed the roles of vector population dynamics and vector-host-pathogen interactions on the spread of plant pathogens (e.g., Hogenhout et al 2008, Mauck et al 2012, Conway et al 2014. Within food webs, vectors also interact with predators, competitors, and mutualists, and such interactions might affect vector-borne pathogens by altering characteristics of vector populations (Blaustein et al 2010, Seabloom et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…This situation could apply to many vernal-pool and container inhabiting organisms. With most such organisms, it has been demonstrated that predation risk, abundance of food resources, and the presence of conspecifics are important factors affecting this decision with gravid females typically avoiding sites with predators and attracted to sites with indication of abundant food for their offspring [6] , [10] [17] . Regulation of the oviposition behavior of mosquitoes and other bloodsucking insects is an issue that is studied intensively due to its implications for population dynamics, evolutionary trajectories, and pest and disease control [1] , [4] , [10] , [11] , [18] [25] .…”
Section: Introductionmentioning
confidence: 99%